Analisa Evaluasi Website Sewa Mobil Pada CV Annur Menggunakan Metode Servqual - Ekky Dede Arlindra Nasution; Eva Zuraidah (STMIK Budi Darma, 2022)
The information system used at CV Annur is in the form of a website https://annur-rent-car.webs.com, the function found on the website which is provided in providing information related to user needs in the form of tracking car rental rates, service points, and ask join. To provide information services, it is necessary to evaluate website performance so that service providers can maintain performance and improve performance where deficiencies are found in performance from the user's point of view. To determine the level of website performance, this research was carried out by applying the servqual method and Importance Performance Analysis. Assessment of user satisfaction is based on five dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Tangibles later each performance attribute will be classified into quadrant I which is a top priority for improving service, quadrant II attributes need to be maintained because they have provided satisfactory service, quadrant III attributes have priority low and quadrant IV attributes are considered less important but the performance is good, the methodology used is descriptive qualitative, and the servqual method is based on 5 dimensions, namely reliability, responsiveness, assurance, tangible, empathy (empathy), testing with validity and reliability tests as well as the value of the gap obtained which must be repaired can be empathy, namely (1.82), responsiveness with a value of gap (1.82) and what must be maintained in reliability with a value of gap (1 .77), tangible with a gap value (1.77), assurance with a gap value (1.79)